"I WAS NOT WARM IN THE COLD". ANOTHER OLD BABYLONIAN PROVERBIAL COLLECTION. (December 2019) - Streck, M. P.; Wasserman, N.
Abstract : BM 108868, an unpublished Old Babylonian tablet containing a collection of moral and existential sayings is edited here for the first time, accompanied by a commentary, photos and a hand-copy. With this discovery, the existence of a solid 2 nd millennium tradition of monolingual Akkadian proverbial sayings is established.